Glass

By regulating the composition of glass materials to achieve a softening point of 720°C or less, the challenges of processing glass into curved surfaces are addressed, resulting in improved devitrification resistance, weather resistance, and workability.

JP2025039878APending Publication Date: 2025-03-21NIPPON ELECTRIC GLASS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025006678
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-06-24
Filing Date
2025-01-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing glass materials with high softening points, such as soda-lime glass with a softening point of about 750°C, are difficult to process into curved surfaces, leading to reduced mold life, dimensional instability, and compromised weather resistance and devitrification resistance.

Method used

A glass composition with a controlled softening point of 720°C or less, achieved by regulating the content of SiO2, Al2O3, B2O3, Li2O, Na2O, K2O, CaO, ZnO, and other components, to enhance devitrification resistance, weather resistance, and workability for curved surface processing.

Benefits of technology

The glass composition with a softening point of 720°C or less improves devitrification resistance, weather resistance, and surface workability, allowing for effective curved surface processing while minimizing thermal deterioration of molds and maintaining glass stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039878000001
    Figure 2025039878000001
  • Figure 2025039878000002
    Figure 2025039878000002
Patent Text Reader

Abstract

To provide a glass satisfying all of curved surface processability, devitrification resistance and weather resistance.SOLUTION: A glass of the invention includes, as a glass composition, 40-70% of SiO2, 0-20% of Al2O3, 0-15% of B2O3, 0-15% of Li2O, 8.6-25% of Na2O, 0-1% of K2O, 2-15% of CaO and 1.5-15% of ZnO in terms of mol%. The glass has a softening point of 720°C or below.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass having a low softening point suitable for curved surface processing (thermal processing). [Background technology]

[0002] In recent years, head-mounted displays that have been developed include devices that project images onto a display hanging from the brim of a hat, glasses-type devices that show both the outside scenery and images on a display, and devices that display images on a see-through light guide plate.

[0003] In devices that display images on a see-through light guide plate, you can see the images displayed on the light guide plate while looking at the outside scenery through glasses. It is also possible to realize 3D display by using technology to project different images on the left and right, and to realize a virtual reality space by using technology to connect the crystalline lens of the eye to the retina.

[0004] These devices require optical members having curved surfaces, and these optical members are produced by processing a glass plate (plate-shaped glass) into a curved surface. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US Patent Application Publication No. 2017 / 283305 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0006] When a glass sheet is curved, it needs to be heat-treated at a temperature equal to or higher than the softening point, but if the heat-treatment temperature is high, the life of the mold used for curved surface processing is shortened. If curved surface processing is performed at a low temperature in order to extend the life of the mold, the glass sheet becomes difficult to deform according to the mold, and the dimensional stability is reduced.

[0007] Soda lime glass is commonly used as window glass, but because it has a softening point of approximately 750°C, it is difficult to properly process it into curved surfaces.

[0008] On the other hand, if the softening point of the glass sheet is lowered to improve the curved surface workability, the glass becomes unstable and is prone to devitrification during forming. Furthermore, the weather resistance is reduced, and the displayed image is prone to become unclear.

[0009] The present invention has been made in view of the above circumstances, and its technical object is to create a glass which is capable of satisfying all of the following: curved surface workability, resistance to devitrification, and weather resistance. [Means for solving the problem]

[0010] The inventors of the present invention have found that the above technical problems can be solved by strictly controlling the content of each component of the glass and controlling the softening point to a predetermined range as a result of various experiments, and propose this as the present invention. That is, the glass of the present invention is characterized by having a glass composition containing, in mole percent, 40-70% SiO2, 0-20% Al2O3, 0-15% B2O3, 0-15% Li2O, 8.6-25% Na2O, 0-1% K2O, 2-15% CaO, and 1.5-15% ZnO, and having a softening point of 720°C or less. Here, the "softening point" refers to a value measured based on the method of ASTM C338.

[0011] The glass of the present invention has the content of each component regulated as described above. This makes it possible to lower the softening point while improving the devitrification resistance and weather resistance. In particular, the glass of the present invention has the ZnO content regulated to 1.5 mol % or more. This makes it possible to lower the softening point while improving the weather resistance.

[0012] Furthermore, the softening point of the glass of the present invention is regulated to not more than 720° C. This suppresses thermal deterioration of the mold and the like during curved surface processing, and also makes it easier for the glass sheet to change shape by following the shape of the mold.

[0013] Moreover, the glass of the present invention preferably has a glass composition containing, in mole percent, 40-70% SiO2, 4.4-20% Al2O3, 0.1-13.6% B2O3, 0-15% Li2O, 13-25% Na2O, 0-1% K2O, 2-10% CaO, 0-2% SrO, 0-2% BaO, and 2-15% ZnO, and has a softening point of 700°C or lower.

[0014] The glass of the present invention is preferably in the form of a plate.

[0015] The glass of the present invention is preferably curved.

[0016] Furthermore, the glass of the present invention preferably has at least one surface having a surface roughness Ra of 0.1 to 5 μm, where "surface roughness Ra" refers to the arithmetic mean roughness Ra defined in JIS B0601-2001.

[0017] The glass of the present invention preferably has a plate thickness of 0.1 to 3 mm.

[0018] The glass of the present invention preferably has a functional film on at least one surface, and the functional film is any one of an anti-reflection film, an anti-fouling film, a reflective film, and an anti-scratch film.

[0019] The glass of the present invention is preferably formed by an overflow downdraw method.

[0020] The glass of the present invention has a viscosity of 10 at the liquidus temperature. 4.6 It is preferable that the viscosity is dPa·s or more. Here, the "viscosity at the liquidus temperature" can be measured by the platinum ball pull-up method. The "liquidus temperature" can be calculated by placing the glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains on the 50 mesh (300 μm) in a platinum boat, and then holding it in a temperature gradient furnace for 24 hours to measure the temperature at which crystals precipitate.

[0021] The glass of the present invention is also preferably used for sensor members or optical component members mounted on vehicles.

[0022] The glass of the present invention is also preferably used for sensors or optical components mounted on vehicles.

[0023] The glass of the present invention is preferably used as a sensor member for measuring the distance between vehicles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The glass of the present invention is characterized by containing, in mole percent, SiO2 40-70%, Al2O3 0-20%, B2O3 0-15%, Li2O 0-15%, Na2O 8.6-25%, K2O 0-1%, CaO 2-15%, and ZnO 1.5-15% as a glass composition. The reasons for limiting the content of each component as described above are as follows. In addition, in the explanation of the content of each component, % indicates mol % unless otherwise specified.

[0025] SiO2 is the main component that forms the skeleton of glass. If the content of SiO2 is too low, Young's modulus, acid resistance, and weather resistance are likely to decrease. Therefore, the preferred lower limit range of SiO2 is 40% or more, 45% or more, 50% or more, 52% or more, 55% or more, 57% or more, 60% or more, and particularly 61% or more. On the other hand, if the content of SiO2 is too high, in addition to the softening point being unduly increased, devitrified crystals are likely to precipitate, and the liquidus temperature is likely to increase. Therefore, the preferred upper limit range of SiO2 is 70% or less, 69% or less, 68% or less, 67% or less, 66% or less, 65% or less, 64% or less, 63% or less, 62% or less, and particularly 61% or less.

[0026] Al2O3 is a component that increases Young's modulus and weather resistance. The preferred lower limit of Al2O3 is 0% or more, 1% or more, 3% or more, 4% or more, 4.4% or more, 4.6% or more, 5% or more, 5.5% or more, and particularly 6% or more. On the other hand, if the content of Al2O3 is too high, the high temperature viscosity increases and curved surface workability tends to decrease. Therefore, the preferred upper limit of Al2O3 is 20% or less, less than 15%, 12% or less, 11% or less, less than 10%, and particularly 9% or less.

[0027] B2O3 is a component that forms the skeleton of glass and acts as a flux. If the content of B2O3 is too low, the liquidus temperature is likely to decrease. Therefore, the preferred lower limit range of B2O3 is 0% or more, 0.1% or more, 0.3% or more, 0.5% or more, 1% or more, 2% or more, 3% or more, and particularly 4% or more. On the other hand, if the content of B2O3 is too high, the acid resistance and weather resistance are likely to decrease. Therefore, the preferred upper limit range of B2O3 is 15% or less, 14% or less, 13.6% or less, 13% or less, 11% or less, 10% or less, 9.5% or less, 8.5% or less, 8% or less, 7.5% or less, 7% or less, and particularly 6.5% or less.

[0028] Alkali metal oxides (Li2O, Na2O, K2O) are components that lower the softening point, but if they are introduced in large amounts, the viscosity of the glass decreases too much, making it difficult to ensure a high liquidus viscosity. In addition, Young's modulus, weather resistance, and electrical resistivity tend to decrease. Therefore, the preferred lower limit range of the total amount of Li2O, Na2O, and K2O is 8.6% or more, 10% or more, 13% or more, 14% or more, 15% or more, 16% or more, 17% or more, and particularly 18% or more, and the preferred upper limit range is 27% or less, 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, 20% or less, and particularly 19% or less. The preferred upper limit range of Li2O is 15% or less, 10% or less, 8% or less, 7% or less, 6% or less, 5% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, and particularly 0.1% or less. The preferred lower limit range of Na2O is 8.6% or more, 10% or more, 12% or more, 13% or more, 14% or more, 15% or more, 16% or more, particularly 17% or more, and the preferred upper limit range is 25% or less, 24% or less, 23% or less, 22% or less, 21% or less, 20% or less, 19% or less, particularly 18% or less. The preferred lower limit range of K2O is 0% or more, particularly 0.1% or more, and the preferred upper limit range is 5% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, particularly 0.1% or less. Note that the raw material for introducing K2O contains more harmful impurities (e.g., radiation-emitting elements, coloring elements) than the raw materials for introducing other components. Therefore, when emphasis is placed on the viewpoint of removing harmful impurities, the content of K2O is preferably 1% or less, 0.5% or less, particularly 0.1% or less.

[0029] The molar ratio (Na2O-Al2O3) / SiO2 is preferably more than 0, 0.05 or more, 0.1 or more, 0.11 to 0.5, 0.12 to 0.3, and particularly 0.15 to 0.25. If the molar ratio (Na2O-Al2O3) / SiO2 is too small, the softening point is likely to increase. Note that "(Na2O-Al2O3) / SiO2" refers to the value obtained by subtracting the Al2O3 content from the Na2O content and dividing it by the SiO2 content.

[0030] By restricting the molar percentage ratio Na2O / (Li2O+Na2O+K2O) to a predetermined range, it is possible to lower the softening point while improving the devitrification resistance. The preferable lower limit range of the molar percentage ratio Na2O / (Li2O+Na2O+K2O) is 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, and particularly more than 0.95. Note that "Na2O / (Li2O+Na2O+K2O)" refers to the value obtained by dividing the Na2O content by the combined amount of Li2O, Na2O, and K2O.

[0031] If the molar percentage ratio Al2O3 / (Li2O+Na2O+K2O) is regulated to a predetermined range, the softening point can be lowered while maintaining weather resistance. The preferred lower limit of the molar percentage ratio Al2O3 / (Li2O+Na2O+K2O) is 0 or more, 0.1 or more, 0.2 or more, 0.25 or more, 0.3 or more, particularly more than 0.35, and the preferred upper limit is 1.1 or less, 1.0 or less, 0.8 or less, 0.7 or less, 0.6 or less, particularly 0.5 or less. Note that "Al2O3 / (Li2O+Na2O+K2O)" refers to the value obtained by dividing the content of Al2O3 by the combined amount of Li2O, Na2O, and K2O.

[0032] MgO, CaO, SrO and BaO are components that lower the softening point. However, if a large amount of MgO, CaO, SrO, BaO and ZnO is introduced, the density becomes excessive, the Young's modulus is easily decreased, and the high-temperature viscosity is too low, making it difficult to ensure a high liquidus viscosity. Therefore, the preferred lower limit range of the total amount of MgO, CaO, SrO and BaO is 2% or more, 2.5% or more, 3% or more, particularly 3.5% or more, and the preferred upper limit range is 20% or less, 18% or less, 15% or less, 12% or less, 10% or less, 8% or less, 6% or less, particularly 4% or less.

[0033] MgO is a component that lowers the softening point, and among alkaline earth metal oxides, it is a component that effectively increases the Young's modulus. However, if the content of MgO is too high, the devitrification resistance and weather resistance are likely to decrease. The preferred lower limit of MgO is 0% or more, 0.1% or more, particularly 0.5% or more, and the preferred upper limit is 15% or less, 10% or less, 8% or less, 5% or less, less than 3%, 2% or less, 1% or less, particularly 0.9% or less.

[0034] CaO is a component that lowers the softening point, and since the raw material used is relatively inexpensive among alkaline earth metal oxides, it is a component that reduces raw material costs. It is also a component that improves weather resistance. However, if the CaO content is too high, devitrification resistance and weather resistance tend to decrease. The preferred lower limit of CaO is 2% or more, 3% or more, 3.1% or more, and particularly 3.7% or more, and the preferred upper limit is 15% or less, 10% or less, 8% or less, 7% or less, 6% or less, and particularly 5% or less.

[0035] The CaO content is preferably greater than the K2O content, more preferably greater than the K2O content by 1 mol % or more, and preferably greater than the K2O content by 2 mol % or more. If the CaO content is less than the K2O content, it becomes difficult to achieve both a low softening point and high devitrification resistance.

[0036] SrO is a component that enhances devitrification resistance, but if the content is too high, the balance of the components in the glass composition is lost, and devitrification resistance is likely to decrease. In addition, harmful impurities are likely to be mixed in from the raw materials introduced. Therefore, the preferred upper limit range of SrO is 10% or less, 3% or less, 2% or less, 1% or less, and particularly 0.1% or less.

[0037] BaO is a component that enhances devitrification resistance, but if its content is too high, the balance of the components in the glass composition is lost, and devitrification resistance is likely to decrease. In addition, harmful impurities are likely to be mixed in from the raw materials introduced. Therefore, the preferred upper limit range of BaO is 10% or less, 3% or less, 2% or less, 1% or less, and particularly 0.1% or less.

[0038] ZnO is a component that lowers the softening point and improves weather resistance, but if its content is too high, the glass is prone to devitrification. Therefore, the preferred lower limit of ZnO is 1.5% or more, 2% or more, 2.5% or more, 3% or more, particularly 3.5% or more, and the preferred upper limit is 15% or less, 10% or less, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, particularly less than 4.8%.

[0039] By restricting the molar percentage ratio CaO / (MgO+CaO+SrO+BaO+ZnO) to a predetermined range, the raw material cost can be reduced and the softening point can be lowered. The preferred lower limit range of the molar percentage ratio CaO / (MgO+CaO+SrO+BaO+ZnO) is 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, particularly 0.8 to 0.95. Note that "CaO / (MgO+CaO+SrO+BaO+ZnO)" refers to the value obtained by dividing the CaO content by the total amount of MgO, CaO, SrO, BaO and ZnO.

[0040] If the molar ratio ZnO / (MgO+CaO+SrO+BaO+ZnO) is regulated within a predetermined range, it is possible to improve weather resistance while maintaining low softening properties. The preferable lower limit range of the molar ratio ZnO / (MgO+CaO+SrO+BaO+ZnO) is 0.1 or more, 0.11 to 1.0, 0.15 to 0.75, 0.2 to 0.55, 0.25 to 0.5, particularly more than 0.3 to 0.4. Note that "ZnO / (MgO+CaO+SrO+BaO+ZnO)" refers to the value obtained by dividing the ZnO content by the total amount of MgO, CaO, SrO, BaO, and ZnO.

[0041] Other components may be incorporated in addition to the above components. From the viewpoint of accurately enjoying the effects of the present invention, the total content of the other components other than the above components is preferably 12% or less, 10% or less, 8% or less, and particularly preferably 5% or less.

[0042] TiO2 and ZrO2 are components that increase acid resistance. However, if the content of TiO2 and ZrO2 is too high, devitrification resistance and transmittance are likely to decrease. In addition, harmful impurities are likely to be mixed in from the raw materials introduced. The preferred upper limit range of TiO2 is 5% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, and particularly less than 0.1%. The preferred upper limit range of ZrO2 is 5% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, and particularly less than 0.1%.

[0043] Fe2O3 is a component that acts as a clarifier and is also a component that is inevitably mixed in as an impurity. The content of Fe2O3 is 0.001 to 0.05%, 0.003 to 0.03%, and particularly 0.005 to 0.019%. If the content of Fe2O3 is too low, high-purity raw materials are required, which tends to increase the raw material cost. On the other hand, if the content of Fe2O3 is too high, the transmittance tends to decrease.

[0044] As a fining agent other than Fe2O3, one or more selected from the group consisting of As2O3, Sb2O3, CeO2, SnO2, F, Cl, and SO3 can be added in an amount of 0 to 2%. However, from an environmental viewpoint, it is preferable that As2O3 and F are not substantially contained, that is, less than 0.1%. In particular, considering the fining ability and environmental impact, SnO2 is preferable as a fining agent. The preferred lower limit range of SnO2 is 0% or more, 0.1% or more, particularly 0.15% or more, and the preferred upper limit range is 1% or less, 0.5% or less, 0.4% or less, particularly 0.3% or less. The preferred lower limit range of Sb2O3 is 0% or more, 0.03% or more, 0.05% or more, particularly 0.07% or more, and the preferred upper limit range is 1% or less, 0.5% or less, 0.4% or less, 0.3% or less, 0.2% or less, particularly 0.1% or less.

[0045] PbO and Bi2O3 are components that reduce high temperature viscosity, but from an environmental standpoint, it is preferable that they are not contained substantially, that is, that their content is less than 0.1%.

[0046] Y2O3, La2O3, Nb2O5, Gd2O3, Ta2O5, and WO3 have the effect of increasing Young's modulus, etc. However, if the content of these components is more than 5%, especially more than 1%, the raw material cost will rise.

[0047] The glass of the present invention preferably has the following properties:

[0048] The softening point is 720° C. or lower, preferably 715° C. or lower, particularly 600 to 700° C. If the softening point is too high, thermal deterioration of the mold and the like tends to progress during curved surface processing, and the glass sheet becomes difficult to change shape by conforming to the shape of the mold.

[0049] The average linear thermal expansion coefficient in the temperature range of 30 to 380°C is preferably 50 × 10 -7 ~125×10 -7 / ℃, 65×10 -7 ~110×10 -7 / ℃, 80×10 -7 ~105×10 -7 / ℃, 85×10 -7 ~100×10 -7 / ℃, especially 88×10 -7 ~98×10 -7 / °C. If the average linear thermal expansion coefficient is outside the above range, it becomes difficult to match the thermal expansion coefficient of various peripheral components (particularly functional films, etc.), and the glass plate is prone to cracking and breakage when incorporated into a device. Note that the "average linear thermal expansion coefficient in the temperature range of 30 to 380°C" refers to a value measured with a dilatometer.

[0050] The liquidus temperature is preferably less than 850° C., 825° C. or less, 800° C. or less, 780° C. or less, 760° C. or less, particularly 750° C. or less. The viscosity at the liquidus temperature is preferably 10 4.6 dPa s or more, 10 5.2 dPa s or more, 10 5.5 dPa s or more, 10 5.8 dPa s or more, especially 10 6.0 dPa·s or more. This makes it easier to form a glass sheet by the down-draw method, particularly the overflow down-draw method, and makes it easier to produce a thin glass sheet. Furthermore, devitrification crystals are less likely to occur in the glass during forming. As a result, it becomes easier to reduce the manufacturing costs of glass sheets.

[0051] High temperature viscosity 10 2.5 The temperature in dPa·s is preferably 1500° C. or less, 1400° C. or less, 1350° C. or less, 1320° C. or less, in particular 1300° C. or less. 2.5 When the temperature at dPa·s increases, the melting property decreases and the manufacturing cost of glass plates rises. 2.5 The "temperature at dPa·s" can be measured using the platinum sphere pulling method.

[0052] In a glass manufacturing process, in order to heat the molten glass, electrodes may be inserted into a melting tank to directly heat the molten glass through electrical current, or the molten glass may be indirectly heated through electrical current by heating a feeder, a forming device, etc. However, when electrically heating the molten glass, if a potential difference occurs between different metal members in contact with the molten glass, an electrical circuit is formed via the molten glass, and bubbles may be generated at the metal / molten glass interface corresponding to the positive and negative electrodes.

[0053] Specifically, when an electrical circuit is formed, the following reaction occurs, which can cause air bubbles to form in the portion that becomes the positive electrode.

[0054] Positive side: O 2- → 0.5O2+ 2e - Negative side: 0.5O2+ 2e - → O 2- According to Faraday's law of electrolysis, the mass of a substance that changes at each electrode through electrolysis is proportional to the amount of electricity flowing (see Equation 1 below). [Number 1] m = (Q M) / (F Z) m: mass of the changed substance (g) Q: Amount of electricity flowing (C) M: molar mass of the substance (g / mol) F: Faraday constant (C / mol) Z: Number of electrons involved in the change of one molecule of material Here, the quantity of electricity Q is expressed as the product of the current I and the time t (see Equation 2). Also, according to Ohm's law, the voltage is expressed as the product of the resistance and the current (see Equation 3). [Number 2] Q = I t I: Current (A) t: time (seconds) [Number 3] E=R·I E: Voltage (V) R: Resistance (Ω) I: Current (A) The resistance R (Ω) is determined by the electrical resistivity ρ (Ω cm) of the glass and the cell constant κ (cm -1 ) (see Equation 4). [Number 4] R=ρ κ R: Resistance (Ω) ρ: Electrical resistivity (Ω cm) κ: Cell constant (cm -1 ) From Equations 2 to 4, the relationship between the quantity of electricity Q and the electrical resistivity ρ is expressed as Equation 5, and the quantity of electricity Q and the electrical resistivity ρ are inversely proportional. In other words, it can be seen that the higher the electrical resistivity ρ, the smaller the quantity of electricity Q becomes, and the mass m of the changed substance = the amount of bubbles decreases. [Number 5] Q = (E t) / (ρ κ) Furthermore, the viscosity of molten glass during molding is approximately constant regardless of the glass composition, so the higher the electrical resistivity at the same viscosity, the smaller the amount of bubbles that are generated during molding.

[0055] Therefore, it is preferable that the electrical resistivity of the molten glass is high. 5.0 The electrical resistivity Logρ in dPa·s is preferably 0.5 Ω·cm or more, 0.6 Ω·cm or more, 0.7 Ω·cm or more, 0.8 Ω·cm or more, 0.9 Ω·cm or more, or 1.0 Ω·cm or more, particularly 1.1 to 10 Ω·cm. 5.0 If the electrical resistivity Logρ in dPa·s is too low, bubbles will be generated in the molten glass, resulting in more bubble defects and higher glass manufacturing costs. 5.0 The electrical resistivity Logρ in dPa·s can be measured using the two-terminal method.

[0056] Measurement frequency 1kHz, high temperature viscosity 10 3.0 The electrical resistivity Logρ in dPa·s is preferably 0.1 Ω·cm or more, 0.2 Ω·cm or more, 0.3 Ω·cm or more, 0.4 Ω·cm or more, 0.5 Ω·cm or more, 0.6 Ω·cm or more, particularly 0.7 to 7 Ω·cm. 3.0If the electrical resistivity Logρ in dPa·s is too low, bubbles will be generated in the molten glass, resulting in more bubble defects and higher glass manufacturing costs. 3.0 The electrical resistivity Logρ in dPa·s can be measured using the two-terminal method.

[0057] The Young's modulus is preferably 65 GPa or more, 68 GPa or more, 70 GPa or more, particularly 72 GPa or more. If the Young's modulus is too low, it becomes difficult to maintain the shape when the plate thickness is thin. Here, the "Young's modulus" can be measured by a well-known resonance method.

[0058] The glass of the present invention is preferably formed by a down-draw method, particularly an overflow down-draw method. The overflow down-draw method is a method in which molten glass is made to overflow from both sides of a heat-resistant trough-shaped structure, and the overflowed molten glass is drawn downward while joining at the lower end of the trough-shaped structure to form a glass sheet. In the overflow down-draw method, the surface to be the surface of the glass sheet does not contact the trough-shaped refractory material and is formed in a free surface state. This makes it easier to produce a glass sheet with high surface smoothness.

[0059] As a method for forming a glass sheet, other than the overflow downdraw method, for example, a slot down method, a redraw method, a float method, a roll out method, etc. can also be adopted.

[0060] As described above, the glass of the present invention has a low softening point, and therefore can be appropriately curved according to the shape of a mold or the like. Therefore, the glass of the present invention is preferably curved in a plate shape, and more preferably curved by heat treatment. When a curved shape is formed by curved processing, the radius of curvature of the curved surface is preferably 100 to 2000 mm, particularly 200 to 1000 mm. This makes it easier to apply the glass to members for head mounted displays.

[0061] The glass of the present invention preferably does not have a compressive stress layer formed on the surface thereof due to ion exchange, which makes it possible to reduce the manufacturing costs of the glass.

[0062] The glass of the present invention preferably has a plate shape, and the plate thickness is preferably 3.0 mm or less, 2.5 mm or less, 2.0 mm or less, 1.5 mm or less, 1.0 mm or less, particularly 0.9 mm or less. The thinner the plate thickness, the easier it is to reduce the weight of the glass plate and to perform curved surface processing. On the other hand, if the plate thickness is too thin, the strength of the glass plate itself decreases. Therefore, the plate thickness is preferably 0.1 mm or more, 0.2 mm or more, 0.3 mm or more, 0.4 mm or more, 0.5 mm or more, 0.6 mm or more, particularly more than 0.7 mm.

[0063] In the glass of the present invention, the surface roughness Ra of at least one surface is preferably 0.1 to 5 μm, particularly 0.3 to 3 μm. When curved surface processing is performed by heat treatment using a mold, it is preferable to restrict the surface roughness Ra of the surface in contact with the mold to 0.1 to 5 μm, particularly 0.3 to 3 μm. In this way, the efficiency of curved surface processing can be improved without making the displayed image unclear. If the surface roughness Ra of the surface in contact with the mold is large, the surface roughness Ra can be reduced by fire polishing the surface.

[0064] The glass of the present invention has a plate shape and has a functional film on at least one surface, and the functional film is preferably any one of an anti-reflection film, an anti-fouling film, a reflective film, and an anti-scratch film.

[0065] The anti-reflection film is preferably a dielectric multilayer film in which low-refractive index layers with relatively low refractive index and high-refractive index layers with relatively high refractive index are alternately laminated. This makes it easier to control the reflectance at each wavelength. The anti-reflection film can be formed by, for example, a sputtering method or a CVD method. The reflectance of the anti-reflection film at each wavelength (particularly, wavelengths of 400 to 700 nm) is preferably, for example, 1% or less, 0.5% or less, 0.3% or less, and particularly 0.1% or less.

[0066] The antifouling film is preferably prepared by coating a solution of a silane compound having a fluoroalkyl group or a fluoroalkyl ether group, the fluorine-containing silane compound being preferably a silazane or an alkoxysilane. Among the silane compounds having a fluoroalkyl group or a fluoroalkyl ether group, the silane compound is preferably a silazane or an alkoxysilane, the fluoroalkyl group in the silane compound being bonded to a Si atom at a ratio of one or less per Si atom, and the remaining silane compounds being hydrolyzable groups or siloxane bond groups. The hydrolyzable group referred to here is, for example, a group such as an alkoxy group, which becomes a hydroxyl group by hydrolysis, and the silane compound forms a polycondensate.

[0067] The reflective film is preferably a metal film such as Al, and the scratch-resistant film is preferably an inorganic film such as SiO2 or Si3N4.

[0068] As described above, the glass of the present invention is suitable as a member for a head-mounted display. In addition, it is preferably used for a sensor member (particularly a sensor member for measuring the distance between vehicles) mounted on a vehicle or a member for an optical component.

[0069] Sensor components mounted on vehicles include photodiodes for LiDAR (Light Detection and Ranging) to measure the distance between vehicles. Generally, photodiodes are manufactured by mounting them in a package made of resin, ceramic, metal, etc., in order to improve weather resistance and resistance to external shocks, and then sealing them with a cover glass that has as little thermal expansion difference as possible with the package.

[0070] The cover glass for this application may be formed with an anti-reflection film to prevent the reflected light of the incident light or the light reflected by the photodiode from being reflected again and entering the photodiode, resulting in noise. In addition, ultraviolet light, visible light, near-infrared light, etc. are used as light sources for measuring vehicle distances, but in recent years, near-infrared light, which is relatively less affected by the spectrum of sunlight, and particularly light in the 920 to 960 nm band (for example, central wavelength 940 nm) are often used. In the future, infrared light in the 900 to 1690 nm band, which is even less affected by sunlight, may be used. Therefore, the anti-reflection film for this application preferably reflects light with a wavelength of 900 nm or more, and the reflectance of the anti-reflection film in the wavelength range of 900 to 1690 nm (particularly the wavelength of 940 nm) is preferably 1% or less, 0.5% or less, 0.3% or less, and particularly 0.1% or less. The reflectance of the anti-reflection film may have a minimum value in a wavelength region of 900 nm or more, and the wavelength region showing the minimum value preferably coincides with the central wavelength of the light source. EXAMPLES

[0071] The present invention will be described below based on examples. Note that the following examples are merely illustrative and the present invention is not limited to the following examples.

[0072] Tables 1 and 2 show examples of the present invention (samples Nos. 1 to 20) and comparative examples (samples Nos. 21 and 22).

[0073] [Table 1]

[0074] [Table 2]

[0075] First, a glass batch prepared by mixing glass raw materials to obtain the glass composition shown in the table was placed in a platinum crucible and melted at 1200 to 1500°C for 4 hours. When melting the glass batch, a platinum stirrer was used to stir and homogenize the glass. Next, the obtained molten glass was poured onto a carbon plate and formed into a plate shape, and then slowly cooled from a temperature about 20°C higher than the annealing point Ta to room temperature at a rate of 3°C / min. The average linear thermal expansion coefficient α, density ρ, strain point Ps, annealing point Ta, softening point Ts, high temperature viscosity 10 4.0 Temperature in dPa·s, high temperature viscosity 10 3.0 Temperature in dPa·s, high temperature viscosity 10 2.5 Temperature in dPa·s, measurement frequency 1kHz, high temperature viscosity 10 5.0 Electrical resistivity Logρ in dPa·s Measurement frequency 1kHz, high temperature viscosity 10 3.0 The electrical resistivity Logρ in dPa·s, the liquidus temperature TL, the viscosity η at the liquidus temperature TL, and the weather resistance were evaluated.

[0076] The average linear thermal expansion coefficient α in the temperature range of 30 to 380° C. is a value measured with a dilatometer.

[0077] The density ρ is a value measured by the well-known Archimedes method.

[0078] The strain point Ps, annealing point Ta, and softening point Ts are values ​​measured based on the method of ASTM C336 or ASTM C338.

[0079] High temperature viscosity 10 4.0 dPa·s, 10 3.0 dPa·s, 10 2.5 The temperature in dPa·s was measured by the platinum sphere pulling method.

[0080] Measurement frequency 1kHz, high temperature viscosity 10 5.0 Electrical resistivity Logρ in dPa·s and measurement frequency 1kHz, high temperature viscosity 10 3.0 The electrical resistivity Logρ in dPa·s was measured by the two-terminal method.

[0081] The liquidus temperature TL is the temperature at which crystals precipitate, measured by placing the glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains on a 50 mesh (300 μm) in a platinum boat and holding it in a temperature gradient furnace for 24 hours. The viscosity η at the liquidus temperature TL is the viscosity of the glass at the liquidus temperature TL, measured by the platinum ball pull-up method.

[0082] The Young's modulus is a value measured by the well-known resonance method.

[0083] Weather resistance was evaluated by the HAST test. Specifically, each sample was kept at 121°C, 95% humidity, and 2 atm for 24 hours, after which the sample was rated as "○" if no peeling or cracks occurred on the glass surface, and "×" if peeling and / or cracks occurred.

[0084] As is clear from the table, samples No. 1 to No. 20 have a softening point Ts of 697°C or less and a viscosity η at the liquidus temperature TL of 10 4.0 Thus, samples No. 1 to No. 20 have good curved surface workability, resistance to devitrification, and weather resistance. On the other hand, samples No. 21 and No. 22 have softening points Ts of 837°C and 977°C, respectively, which makes them difficult to process into curved surfaces. EXAMPLES

[0085] The glass (sheet thickness 0.8 mm) of samples No. 1 to 20 was curved at a temperature near the softening point Ts to match the shape of a mold, and then a concave mirror was produced by forming an Al reflective film on the surface on the recessed side where the display light was to be reflected.

[0086] On the other hand, for the glasses (sheet thickness 0.8 mm) of Samples 21 and 22, curved surfaces were processed at a temperature near the softening point Ts so as to follow the shape of the mold. However, because the temperature during curved surface processing was high, thermal degradation of the mold was observed. [Industrial Applicability]

[0087] The glass of the present invention is suitable for use as a member for a head-mounted display because of its excellent curved surface processability, devitrification resistance, and weather resistance. In addition, because of its excellent devitrification resistance and weather resistance, the glass is also suitable for use as a cover glass for CCD or CMOS type image pickup elements and a cover glass for photodiodes in LiDAR (Light Detection and Ranging) for measuring inter-vehicle distances. Because of its excellent curved surface processability (thermal processability) and weather resistance, the glass is also suitable for use as a medical tubular glass.

Claims

1. The glass composition is, in mol%, SiO 2 40-70%, Al 2 O 3 0-20%, B 2 O 3 2-15%, Li 2 O 0-15%, Na 2 O 10-25%, K 2 A glass containing 0-1% O, 2-15% CaO, and 1.5-15% ZnO, and having a softening point of 720° C. or lower, which is used for a member for a head mounted display.

2. The glass composition is, in mol%, SiO 2 40-70%, Al 2 O 3 0-20%, B 2 O 3 2-15%, Li 2 O 0-15%, Na 2 O 10-25%, K 2 A glass containing 0-1% O, 2-15% CaO, and 1.5-15% ZnO, and having a softening point of 720° C. or lower, which is used for a sensor member or an optical component member mounted on a vehicle.

3. The glass composition is, in mol%, SiO 2 40-70%, Al 2 O 3 0-20%, B 2 O 3 2-15%, Li 2 O 0-15%, Na 2 O 10-25%, K 2 A glass containing 0-1% O, 2-15% CaO, and 1.5-15% ZnO, having a softening point of 720° C. or lower, and used as a sensor member for measuring the distance between vehicles.

4. The glass composition is, in mol%, SiO 2 40-65%, Al 2 O 3 4.4-20%, B 2 O 3 0.1-13.6%, Li 2 O 0-15%, Na 2 O 13-25%, K 2 O 0-1%, CaO 2-10%, SrO 0-2%, BaO 0-2%, ZnO 1.5-15%, Fe 2 O 3 4. The glass according to claim 1, containing 0.001 to 0.05% of Mo and having a softening point of 720° C. or lower.

5. 5. The glass according to claim 1, which is in the form of a plate.

6. 6. The glass according to claim 5, characterized in that it is curved.

7. 7. The glass according to claim 1, wherein at least one surface has a surface roughness Ra of 0.1 to 5 μm.

8. 8. The glass according to claim 5, wherein the thickness of the glass is 0.1 to 3 mm.

9. 9. The glass according to claim 5, further comprising a functional film on at least one surface thereof, the functional film being any one of an anti-reflection film, an anti-fouling film, a reflective film, and an anti-scratch film.

10. Viscosity at liquidus temperature is 10 4.6 10. The glass according to claim 1, having a viscosity of at least dPa·s.

Citation Information

Patent Citations

  • Glass for light transmission body with superior weather resistance

    JP1980051733A

  • Optical glass for prism, method for producing the same, and optical component for prism

    JP2003292339A

  • Cover glass for solid imaging element and its manufacturing method

    JP2005200289A

  • Optical glass of dense barium flint position

    JP2008297198A

  • High index glass and devices incorporating such

    US20170283305A1